Increased Protein Stability and Interleukin-2 Production of a LATG131D Variant With Possible Implications for T Cell Anergy - Arbulo-Echevarria, Mikel M.; Vico-Barranco, Inmaculada; Narbona-Sánchez, Isaac; García-Cózar, Francisco; Miazek, Arkadiusz; Aguado, Enrique (Frontiers in Cell and Developmental Biology, 2020)
The adaptor LAT plays a crucial role in the transduction of signals coming from the TCR/CD3 complex. Phosphorylation of some of its tyrosines generates recruitment sites for other cytosolic signaling molecules. Tyrosine 132 in human LAT is essential for PLC- activation and calcium influx generation. It has been recently reported that a conserved glycine residue preceding tyrosine 132 decreases its phosphorylation kinetics, which constitutes a mechanism for ligand discrimination. Here we confirm that a LAT mutant in which glycine 131 has been substituted by an aspartate (LATG131D) increases phosphorylation of Tyr132, PLC- activation and calcium influx generation. Interestingly, the LATG131D mutant has a slower protein turnover while being equally sensitive to Fas-mediated protein cleavage by caspases. Moreover, J.CaM2 cells expressing LATG131D secrete greater amounts of interleukin-2 (IL-2) in response to CD3/CD28 engagement. However, despite this increased IL-2 secretion, J.CaM2 cells expressing the LATG131D mutant are more sensitive to inhibition of IL-2 production by pre-treatment with anti-CD3, which points to a possible role of this residue in the generation of anergy. Our results suggest that the increased kinetics of LAT Tyr132 could contribute to the establishment of T cell anergy, and thus constitutes an earliest known intracellular event responsible for the induction of peripheral tolerance.